Sikap Mahasiswa Non Muslim Dalam Mengikuti Pelajaran Arab Melayu Angkatan 2021 PBSI Universitas Riau - Hafzah Harja; Endah Melani; Anisa Putri; Hasnah Faizah (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This article aims to analyze the attitude of Non-Muslim students in the context of learning Malay Arabic in the Indonesian Language and Literature Study Program (PBSI) Riau University in 2021. The data collection method used in this research is descriptive qualitative. The data in this study are questionnaires and interviews conducted with Non-Muslim students of the 2021 batch of the Indonesian Language and Literature Education Study Program at Riau University. Non-Muslim students showed a positive attitude, openness, and dedication to the subject matter, facing the challenges of language, culture, and values contained in this subject. The main focus is the learning spirit shown by Non-Muslim students during the learning process of Arabic Malay. Although the subject matter is related to religious aspects, Non-Muslim students showed appreciation and openness to Islamic values and traditions taught in the context of Malay Arabic. The results of this study provide important insights for curriculum development as well as more inclusive teaching strategies, to ensure that learning Malay Arabic in Riau University's PBSI environment provides balanced and beneficial benefits for all students, regardless of their religious background.